Effectiveness of a Flipped Classroom in Learning Periodontal Diagnosis and Treatment Planning. Issue 6 (1st June 2018) - Lee, Cliff; Kim, Soo-Woo
Abstract : The aim of this study was to assess whether a flipped classroom was an effective model for dental students to learn periodontal diagnosis and treatment planning (DTP). Participants were all third‐year students in three academic years (2015–17) at Harvard School of Dental Medicine: two groups that experienced the flipped classroom (Classes of 2017 and 2018), and a control group (Class of 2019) that received the same content in traditional lecture format. All three groups completed a DTP knowledge quiz before and after the educational experience; the flipped classroom groups also completed pre and post surveys of their opinions about flipped classrooms. The flipped classroom group received a 23‐minute video and corresponding PowerPoint presentation to view on their own time. In class, these students were divided into groups to diagnosis and treatment plan cases and discuss them with the instructor. Of 71 students in the two flipped classroom groups, 69 pre and post quizzes were returned (response rate 97%), and 61 pre and post surveys were returned (response rate 86%). Of 35 students in the lecture group, 34 completed pre and post quizzes (response rate 97%). The mean pre scores on the knowledge quiz in the flipped classroom groups and the conventional lecture group were 64% and 54%, respectively. After the DTP education, students' quiz scores improved in all three groups, but only the difference in the flipped classroom groups was statistically significant (p<0.01). After the flipped classroom session, 84% of the students agreed or strongly agreed that this methodology was effective for learning periodontal DTP, and 90% agreed or strongly agreed they understood the fundamentals of periodontal DTP—both increases over their pre survey scores. Overall, this flipped classroom model was effective in educating students on periodontal DTP and was well received by the students.